KECERDASAN EMOSI (EMOTIONAL INTELLIGENCE) DALAM TASAWUF - Gitosaroso, Moh. (Khatulistiwa, 2012)
Emotion is the power without limit, the vital energy which is beneficial for success in life; Successful at learning, at work, at home, in the community, in a relationship with oneself aas well as with God. To realize it, it depends on on a person's ability to control and harness the emotion effectively, efficiently and professionally.